Comparison of microparticle transport and deposition in nasal cavity of three different age groups - Corda, John Valerian; Shenoy, B. Satish; Ahmad, Kamarul Arifin; Lewis, Leslie; Prakashini, K.; Rao, Anoop; Zuber, Mohammad (Taylor and Francis Ltd., 2024)
Objective: The nasal cavity effectively captures the particles present in inhaled air, thereby preventing harmful and toxic pollutants from reaching the lungs. This filtering ability of the nasal cavity can be effectively utilized for targeted nasal drug delivery applications. This study aims to understand the particle deposition patterns in three age groups: neonate, infant, and adult. Materials and methods: The CT scans are built using MIMICS 21.0, followed by CATIA V6 to generate a patient-specific airway model. Fluid flow is simulated using ANSYS FLUENT 2021 R2. Spherical monodisperse microparticles ranging from 2 to 60 µm and a density of 1100 kg/m3 are simulated at steady-state and sedentary inspiration conditions. Results: The highest nasal valve depositions for the neonate are 25 for 20 µm, for infants, 10 for 50 µm, 15 for adults, and 15 for 15 µm. At mid nasal region, deposition of 15 for 20 µm is observed for infant and 8 for neonate and adult nasal cavities at a particle size of 10 and 20 µm, respectively. The highest particle deposition at the olfactory region is about 2.7 for the adult nasal cavity for 20 µm, and it is <1 for neonate and infant nasal cavities. Discussion and conclusions: The study of preferred nasal depositions during natural sedentary breathing conditions is utilized to determine the size that allows medication particles to be targeted to specific nose regions.